Decision support system in determining the priority of disaster mitigation infrastructure development in villages level using the Simple Additive Weight (SAW) method. Issue 1 (April 2021) - Rasadi, A; Hidayat, B; Ophiyandri, T
Abstract: Disasters are a global problem now. Particularly in Indonesia, disaster management has entered a new paradigm, from previously only focusing on emergency response activities and using mitigation and preparedness approaches. Mitigation and preparedness are carried out when a disaster does not occur. Disaster mitigation or mitigation needs to be integrated with disaster risk reduction efforts into development for the sake of sustainability and mainstreaming disaster risk reduction into village program and activity planning. In other words, a disaster risk analysis must be one of the bases in planning sustainable development. The construction of facilities and infrastructure for disaster management is also one of the priorities in village development. However, village infrastructure development planning that has been implemented has not yet considered the disaster management aspects. In this study, a decision support system model (simple additive weight, SAW) was designed, which considers aspects of disaster management that are integrated into the village development planning process.